ANALISIS PENGARUH BEKERJA DARI RUMAH, BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP EFEKTIVITAS KERJA KARYAWAN KEBUN SEHAT JSR - Andriani, Desika; Arya Wardana, Meliano (Management Research and Business Journal, 2023)
ABSTRACT This study aims to analyze the influence of working from home, organizational culture and competence on the work effectiveness of JSR HEALTHY KEBUN employees. The data used in this study are primary data sourced from questionnaires filled out directly by the respondents. Data collection uses a questionnaire that has been tested for validity and reliability. Hypothesis testing is carried out using multiple linear regression analysis by first carrying out the classical assumption test which includes the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results of the validity test showed that all statements used to measure the variables used in this study had a correlation coefficient that was greater than rtable 0.3202 (rtable value for n=39), so it could be concluded that each question item was valid . The results of the reliability test showed that the Cronbach Alpha value was 0.916 > 0.60 so it could be concluded that the instruments used for the variables Working From Home, Organizational Culture and Competence on Work Effectiveness could be said to be reliable. Based on the test of the coefficient of determination (r2) it can be concluded that the independent variables Work From Home (X1), Organizational Culture (X2), Competence (X3), in this study were able to explain 81.6% regarding Employee Effectiveness (Y). While the remaining 18.4% is influenced by other factors not examined. Multiple linear regression analysis serves to prove the research hypothesis. The data that has been processed produces the following regression equation: Y = 10.826 + 0.224 X1 + 0.331 X2 + 0.184 X3 The results show that Working From Home, Organizational Culture and Competence have a positive and significant influence on Work Effectiveness. The results of testing the t-test hypothesis show that the Working From Home, Organizational Culture and Competence variables studied are proven to significantly influence the Employee Work Effectiveness variable partially because they have tcount > ttable and a significance level of less than 0.05. Then through the F statistical test, the results are Ftable (57.191 > 2.87). This can indicate that Working From Home, Organizational Culture and Competence have a significant effect on Employee Work Effectiveness.